Perceived childhood exposure to domestic violence: The risk for adult revictimisation - Ryan, Jill; Rich, Edna; Roman, Nicolette V. (Social and Health Sciences, 2023)
The prevalence of domestic violence is described as pervasive with a majority of victims being females and perpetrators being males. Often females who experienced domestic violence had been previously exposed to family violence during childhood. The aim of the study was therefore to investigate the perceived childhood exposure to domestic violence as a predisposing factor for revictimisation in adulthood. The study used a quantitative approach with a cross-sectional correlation design. The sample consisted of 77 female participants from shelters across Cape Town, Western Cape. The study employed an adapted version of the Child Exposure to Domestic Violence (CEDV) Scale. The questionnaire was divided into three sections, namely demographic details, types of exposure to domestic violence the adult may have experienced as a child, and current adult experiences of domestic violence. The data was analysed using the Statistical Package for Social Sciences V21 (SPSS). Results suggest that there is a significant positive relationship between past perceived experiences of domestic violence and present perceived experiences of domestic violence. Limitations and recommendations are stipulated for proposed intervention strategies and further study expansion on this topic.